The Use of Personal Protective Equipment on Ulumbu Thermal Power Plant Workers in Manggarai Regency - Watu, Laurensia Juviani; Berek, Noorce Ch; Riwu, Rut Rosina (Faculty of Public Health, Nusa Cendana University, 2021)
The use of Personal Protective Equipment (PPE) is one way to avoid the danger of accidents that are used by workers to protect all or part of their bodies from the potential hazards of work accidents. The purpose of this study is to describe the use of personal protective equipment for thermal power plant workers in the Manggarai Regency. This research is descriptive. The sample in this study amounted to 55 workers at PLTP Ulumbu, Manggarai Regency, which were taken using a total sampling technique. The results showed that the workforce at PLTP Ulumbu had good knowledge about the use of PPE (100%), had a good attitude towards the use of PPE (89.09%), and used complete PPE when working (72.72%). It is recommended for owners of PLTP Ulumbu to provide counseling and training on PPE for workers at PLTP Ulumbu so that it can be used as an evaluation to achieve Occupational Health and Safety in the workplace and can improve supervision of workers in terms of the use of PPE at work. For workers at PLTP Ulumbu to always wear complete PPE even though they are resting around the work area and each worker is responsible for caring for PPE.